Intra‐population variation in anemia status and its relationship to economic status and self‐perceived health in the Mexican Family Life Survey: Implications for bioarchaeology. Issue 2 (27th May 2014) - Piperata, Barbara A.; Hubbe, Mark; Schmeer, Kammi K.; Reitsema, Laurie J.; McIlvaine, Britney Kyle
ABSTRACT Recently scholars have advocated for the use of a critical biocultural approach in bioarchaeology, where osteological and dental markers of stress are used to understand the broader biosocial context of past populations. However, the ability to accomplish this task rests on the assumption that ultimate‐level environmental stressors and well‐being in the past can be reconstructed from the prevalence of pathologies in skeletal collections. Here we test this assumption using anemia prevalence in the Mexican Family Life Survey. Specifically we test three hypotheses: (1) that individuals sharing the same household are more likely to share anemia status; (2) anemia status is a predictor of economic status (a common proxy for broader environmental context); and (3) anemia status is related to self‐rated health. Results demonstrate that: anemia status was not commonly shared between household members; there was a significant overlap in economic status between anemic and nonanemic individuals (i.e., anemia poorly predicted economic status) and; while anemia status was associated with self‐perceived health, the majority of those who reported poor health were nonanemic while a significant number of those who reported very good health were anemic. We argue that these findings are likely related to variation in individual frailty, which is shaped by biological and cultural risk factors. Therefore, we advocate for greater incorporation of individual frailty into bioarchaeological investigations, and, in effort to overcome some of the difficulties associated with this task, increased use of data from living populations and greater collaboration between bioarchaeologists and human biologists. Am J Phys Anthropol 155:210–220, 2014. © 2014 Wiley Periodicals, Inc.